2021
DOI: 10.1093/aesa/saab053
|View full text |Cite
|
Sign up to set email alerts
|

Directed Sequencing of Plant Specific DNA Identifies the Dietary History of Four Species of Auchenorrhyncha (Hemiptera)

Abstract: Auchenorrhyncha (Hemiptera) includes several families of sap-feeding insects that tend to feed on a wide-range of host plants. Some species within Auchenorrhyncha are major agricultural pests that transmit plant pathogens or cause direct feeding damage. Nearly all pest Auchenorrhyncha are highly polyphagous, have mobile nymphs, and colonize crops from noncrop habitats. We examined whether methods for gut content analysis developed for more specialized Hemiptera identify dietary history of polyphagous Auchenorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Our results support previous findings of polyphagous feeding behavior of early instars of L. delicatula [ 1 , 14 , 35 ]. Particularly, many authors reported the narrowing pattern of L. delicatula host plant use, from the first instars to adults [ 1 , 3 , 4 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results support previous findings of polyphagous feeding behavior of early instars of L. delicatula [ 1 , 14 , 35 ]. Particularly, many authors reported the narrowing pattern of L. delicatula host plant use, from the first instars to adults [ 1 , 3 , 4 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…We specifically used this published list to determine whether our findings could potentially contribute to and expand the host plant list of L. delicatula . Thirteen novel plant taxa that we reported in this study were also determined by comparison with the findings by Cooper et al [ 14 ], the only study that used DNA metabarcoding of gut contents of the first instars of L. delicatula . We emphasize that these are novel food plants, and whether they support the development and reproduction of L. delicatula could also be a focus for future studies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations